Cancer, Fertility and Me: Developing and Testing a Novel Fertility Preservation Patient Decision Aid to Support Women at Risk of Losing Their Fertility Because of Cancer Treatment - Jones, Georgina L.; Moss, Rachael H.; Darby, Frances; Mahmoodi, Neda; Phillips, Bob; Hughes, Jane; Vogt, Katharina S.; Greenfield, Diana M.; Brauten-Smith, Grete; Gath, Jacqui; Campbell, Tonia; Stark, Daniel; et al. (Frontiers in Oncology, 2022)
Background: Women with a new cancer diagnosis face complex decisions about interventions aiming to preserve their fertility. Decision aids are more effective in supporting decision making than traditional information provision. We describe the development and field testing of a novel patient decision aid designed to support women to make fertility preservation treatment decisions around cancer diagnosis. Methods: A prospective, mixed-method, three stage study involving: 1) co-development of the resource in collaboration with a multi-disciplinary group of key stakeholders including oncology and fertility healthcare professionals and patient partners, 2) alpha testing with a group of cancer patients who had faced a fertility preservation treatment decision in the past (n=11), and oncology and fertility healthcare professionals and stakeholders (n=14) and, 3) beta testing with women in routine care who had received a recent diagnosis of cancer and were facing a fertility preservation treatment decision (n=41) and their oncology and fertility healthcare professionals (n=3). Ten service users also provided feedback via an online survey. Results: A 60-page paper prototype of the Cancer, Fertility and Me patient decision aid was initially developed. Alpha testing of the resource found that overall, it was acceptable to cancer patients, healthcare professionals and key stakeholders and it was considered a useful resource to support fertility preservation treatment decision-making. However, the healthcare professionals felt that the length of the patient decision aid, and elements of its content may be a barrier to its use. Subsequently, the prototype was reduced to 40 pages. During beta testing of the shortened version in routine care, women who received the resource described its positive impact on their ability to make fertility preservation decisions and support them at a stressful time. However, practical difficulties emerged which impacted upon its wider dissemination in clinical practice and limited some elements of the evaluation planned. Discussion: Women receiving the decision aid within the cancer treatment pathway found it helped them engage with decisions about fertility preservation, and make better informed, values-based care plans with oncology and fertility teams. More work is needed to address access and implementation of this resource as part of routine oncology care pathways.